Prevalence of Trachoma in Katsina State, Nigeria: Results of 34 District-Level Surveys. (7th December 2016) - Mpyet, Caleb; Muhammad, Nasiru; Adamu, Mohammed Dantani; Muazu, Habila; Umar, Murtala Mohammad; Goyol, Musa; Onyebuchi, Uwazoeke; Chima, Ima; Idris, Haliru; William, Adamani; Isiyaku, Sunday; Nwobi, Benjamin; et al.
ABSTRACT: Purpose : To determine the local government area (LGA)-level prevalence of trachoma in all 34 LGAs of Katsina State. Methods : A population-based prevalence survey was conducted in each LGA of Katsina State, using the Global Trachoma Mapping Project methodology. We used a 3-stage cluster random sampling strategy to select 25 households from each of 25 clusters. We examined all residents of selected households aged 1 year and older for the clinical signs of trachomatous inflammation–follicular (TF), trachomatous inflammation–intense and trichiasis, using the World Health Organization (WHO) simplified grading scheme. Results : We examined 129, 281 persons. Six LGAs had a TF prevalence ≥10%, and another six LGAs had a TF prevalence between 5% and 9.9%; all 12 require mass drug administration with azithromycin plus other interventions. The prevalence of trichiasis was ≥1.0% in 13 LGAs, and there is a need to perform trichiasis surgery in over 26, 000 persons to reach targets set by the WHO for elimination of trichiasis. Conclusion : The prevalence of TF is generally low in Katsina state, but urgent steps must be taken to implement the full SAFE strategy (surgery, antibiotics, facial cleanliness, environmental improvement) in at least 12 LGAs while also stepping up efforts to provide community-based trichiasis surgery throughout the whole state, in order to make trachoma elimination by 2020 a reality.